On the generation and origin of I/f noise - Kaulakys, B.; Meškauskas, T. (Nonlinear Analysis: Modelling and Control, 1999)
Simple analytically solvable model exhibiting 1/f spectrum in any desirably wide range of frequency is analysed. The model consists of pulses (point process) whose interevent times obey an autoregressive process with small damping. Analysis and generalizations of the model indicate to the possible origin of 1/f noise, i.e. random increments between the occurrence times of particles or pulses resulting in the clustering of the pulses.
Keywords: none